Experimental assessment of tiltrotor air-intake duct shape optimization - Gibertini, G.; Auteri, F.; Campanardi, G.; Grassi, D.; Preatoni, G.; Zagaglia, D.; Zanotti, A. (My University, 2017)
The present paper describes the experimental activity carried out at Politecnico di Milano large wind tunnel in the frame of CleanSky programme to assess the effectiveness of the CFD-based air-intake duct shape optimisation of the European platform tiltrotor ERICA. The tests were carried out on a 1/2.5 scaled model including the nacelle, the external portion of the wing and two interchangeable internal ducts reproducing the baseline and optimised shape. In addition, the model presented the rotor hub equipped with rotating blade stubs. A comprehensive experimental campaign was carried out including model configurations reproducing different forward flight conditions of the aircraft. The assessment of the optimised shape performance was evaluated by comparison of directional probes measurements performed at the Aerodynamic Interface Plane (AIP). Moreover, pressure measurements were also carried out on the duct internal surface. The experimental results confirmed an improved performance of the optimised duct with respect to the baseline configuration not only in cruise, representing the design flight condition considered for the CFD optimisation, but also for conversion condition. Moreover, the present experimental investigation also highlighted that the choice of the blade stubs length is very critical for air-intake performance tests.